White Spot Syndrome Virus Establishes a Novel IE1/JNK/c-Jun Positive Feedback Loop to Drive Replication - Wang, Sheng; Li, Haoyang; Weng, Shaoping; Li, Chaozheng; He, Jianguo (iScience, 2020)
Viruses need to hijack and manipulate host proteins to guarantee their replication. Herein, we uncovered that the DNA virus white spot syndrome virus (WSSV) established a novel positive feedback loop by hijacking the host JNK pathway via its immediate-early 1 (IE1) protein to drive replication. Specifically, the WSSV IE1 bound to host JNK, and enhanced JNK autoactivation by autophosphorylation, and in turn, elevated JNK kinase activity to its substrate c-Jun and induced IE1, which resulted in a viral gene-mediated positive feedback loop. Moreover, the activation of this loop is able to induce wsv056, wsv249, and wsv403, in addition to IE1 itself. Disruption of this loop during WSSV infection by knockdown of JNK, c-Jun or IE1 led to an increased survival rate and lower viral burdens in shrimp. Taken together, this loop may provide a potential target for the development of specific antiviral strategies or agents against WSSV infection. [Display omitted] •Lvc-Jun promotes WSSV IE1 induction via interacting with the promoter of IE1 gene•The interaction of IE1-LvJNK enhances the autophosphorylation of LvJNK•IE1 hijacks the JNK/c-Jun cascade to create a feedback loop to drive replication•wsv056, wsv249, and wsv403 are also benefit from this positive feedback loop Biological Sciences; Molecular Biology; Virology; Molecular Microbiology